Experimental Study on Active Control of Surge in a Centrifugal Compression System - Nie Chaoqun; Chen Jingyi; Chen Naixing (International Journal of Rotating Machinery)
An experimental study has been carried out on the active control of surge in a centrifugal compression system. With a computerized on-line control scheme, the surge phenomenon is suppressed and the stable operating range of the system is extended. In order to design the active control scheme and choose the desired parameters of the control system inputs, special emphases have been placed on the development of surge inception and the nonlinear interaction between the system and the actuator. By use of the method designed in the present work, the results of active control onsurge have been demonstrated for the different B parameters, different prescribed criteria and different control frequencies.